Fruit infiltration with magnesium is a feasible way to predict bitter pit susceptibility in 'Gala' apples grown in Southern Brazil - Amarante C.V.T.* (2005)
Apple fruits cv. 'Gala' were harvested 20 days before anticipated commercial harvest from orchards in Southern Brazil having a historic of high incidence of bitter pit. Fruits were vacuum infiltrated (100 mm Hg/2 min) in 0.1 M MgCl2 (with 0.3 M sorbitol/0.1% Silwet L-77) and held for 14 days at 20°C/60-70% RH when the number of induced pits (NIP) was recorded on individual fruits. Fruits from the same orchards were harvested at the commercial maturity and cold stored (0-2°C/90-95% RH) for four months. These fruits were then left for seven days at 20°C/60-70% RH to allow the full manifestation of bitter pit symptom and them assessed for number of pits (NP) per fruit. Two hundred and twenty-five individual fruits ranging from none to very high levels of pits per fruit from both, infiltrated or cold stored apples, were selected and then analyzed for flesh and skin content of N, K, Ca, and Mg. Tissue mineral status versus fruit susceptibility to bitter pit (NIP for infiltrated fruit) or fruit severity of bitter pit (NP for cold stored fruit) were plotted to predict bitter pit risk based on mineral analysis as well as to assess the viability of fruit infiltration with Mg to predict postharvest risk of bitter pit. The risk of bitter pit was Ca related. The Ca content in the skin tissue provided better prediction of bitter pit risk (NIP and NP) than Ca content in the flesh tissue. For both, infiltrated and cold stored-fruits, apples with a-1 Ca content in the skin and in the flesh lower than 150 mg kg-1 fw and 40 mg kg-1 fw, respectively, showed increasing although variable risk of bitter pit. Therefore, fruit infiltration with Mg represents a valuable tool to assess the risk of bitter pit in 'Gala'.